2016
DOI: 10.1242/jcs.191320
|View full text |Cite
|
Sign up to set email alerts
|

Localized translation regulates cell adhesion and transendothelial migration

Abstract: Epithelial-to-mesenchymal transition (EMT) is a process by which cancer cells gain the ability to leave the primary tumor site and invade surrounding tissues. These metastatic cancer cells can further increase their plasticity by adopting an amoeboid-like morphology, by undergoing mesenchymal-to-amoeboid transition (MAT). We found that adhering cells produce spreading initiation centers (SICs), transient structures that are localized above nascent adhesion complexes, and share common biological and morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…We confirmed that RBM3 co-localized with the cytoskeletal protein vinculin (Fig. 1g ), a known component of SICs 31 , 32 , and that SICs contained the RNA-BP FUS as previously reported 31 , 32 (Fig. 1h ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We confirmed that RBM3 co-localized with the cytoskeletal protein vinculin (Fig. 1g ), a known component of SICs 31 , 32 , and that SICs contained the RNA-BP FUS as previously reported 31 , 32 (Fig. 1h ).…”
Section: Resultssupporting
confidence: 90%
“…SICs are spherical outpouchings of the plasma membrane in which a ring of F-actin circumscribes a cytoplasmic interior containing some focal adhesion proteins, translation machinery, ribosomal and poly A RNA, and RNA-BPs 31 33 . They are “hot spots” of mRNA translation 32 , which is thought to promote the formation of mature focal adhesions 31 , 32 . Insofar as our prior work showed that RBM3 stimulates translation 5 , the detection of RBM3 in SICs raised the possibility that it is a regulator of cell spreading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HaCaT cells are spontaneously immortalized from adult skin keratinocytes and retain full differentiation capacity, while RPE-1 cells are near-diploid human retinal pigment epithelial cells immortalized with human telomerase reverse transcriptase (hTERT; Bodnar et al, 1998;Boukamp et al, 1988). In marked contrast, E4orf4 reduced cell proliferation in several types of cancer cell lines, including triple-negative breast cancer cells with epithelial or mesenchymal properties (MDA-MB-468 and MDA-MB-231, respectively; Bergeman et al, 2016), human bone osteosarcoma epithelial cells (U2OS), prostate carcinoma epithelial cells (22Rv1), and cervix carcinoma epithelial cells (HeLa; Fig. 1 B, Proliferation).…”
Section: Resultsmentioning
confidence: 99%
“…After digestion by EcoRI, this sequence was ligated into EcoRI restriction sites of pLKO.1 vector containing shSUN1 to generate shSUN1-1/2-2 and shSUN1-2/ 2-1. Lentiviral particles were generated by transfecting 293T cells with 12 µg pLKO.1 vector, 6 µg psPAX2 packaging plasmid (Addgene; plasmid #12260), and 2 µg pMD2.G envelope plasmid (Addgene; plasmid #12259), as described previously (Bergeman et al, 2016).…”
Section: Dziengelewski Et Almentioning
confidence: 99%